Respect for patient autonomy as a medical virtue*. (December 2015) - Cook, Thomas; Mavroudis, Constantine D.; Jacobs, Jeffrey P.; Mavroudis, Constantine
Abstract: Respect for patient autonomy is an important and indispensable principle in the ethical practice of clinical medicine. Legal tenets recognise the centrality of this principle and the inherent right of patients of sound mind – properly informed – to make their own personal medical decisions. In the course of everyday medical practice, however, challenging cases may result in ethical dilemmas for the patient, the physician, and society. Resolution of these dilemmas requires a thorough understanding of the underlying principles that allow the clinician to make informed decisions and to offer considered therapeutic options to the patient. We argue in this paper that there is also need for a transition of moral competency from understanding principles to attaining virtue in the classic Aristotelian tradition. Achieving moral virtue is based on a lifetime of learning, practising, and watching how others, who have achieved virtue, act and perform their duties. We further claim that learning moral virtue in medical practice is best realised by incorporating the lessons learnt during daily rounds where frank discussions and considered resolutions can occur under the leadership of senior practitioners who have achieved a semblance of moral excellence.